Short Communication: Biological control of Fusarium wilt on banana plants using biofertilizers - Arief Widyantoro; HADIWIYONO; SUBAGIYA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Widyantoro A, Hadiwiyono, Subagiya. 2020. Biological control of Fusarium wilt on banana plants using biofertilizers. Biodiversitas 21: 2119-2123. Fusarium wilt is an important disease of banana caused by Fusarium oxysporum f. sp. cubense (FOC). The FOC is a weak parasite that attacks many bananas whose conditions are weak such as nutrients. Therefore, controlling Fusarium wilt through fertilization is important so that bananas are not nutrient deficient which can cause plants to be susceptible to FOC. The research aimed to study the effect of biofertilizer applications on FOC suppression in planta. Seven treatments were tested on banana seedlings cv. Ambon Kuning under a completely randomized design: (i) no biofertilizer, (ii) carrier material of biofertilizer, (iii) comparative biofertilizer product, (iv) Azotobacter, (v) Azospirillum, (vi) Streptomyces and (vii) Bacillus. The present study showed that biofertilizer agents were antagonistic to Fusarium wilt. The results showed that biofertilizer agents had the potential to suppress the Fusarium wilt in planta. Streptomyces and Bacillus were the most effective in controlling the Fusarium wilt. Azotobacter and Azospirillum had not been able to prevent the incidence of wilt disease.